The contribution of the university extension to human development and the expansion of capabilities. Analysis of projects of the National University of Costa Rica - Zlateva Peneva, Pepa (2017)
This paper mainly aims to determine the contributions to human development (HD) and the expansion of university extension capabilities the National University of Costa Rica is currently making. The paper analyzes the coherence between the university extension and the values of human development approach welfare, participation, equity and sustainability (Boni and Gasper, 2011). It also seeks to contribute to human development in terms of the capabilities generated in the beneficiary population of three university projects; this contribution would be through the evaluations made by local people and the staff responsible for the projects. We have achieved an approach to the Latin American and Costa Rican extensionist tradition through the programs, projects and extension activities of the National University. In this paper, we present the human development and capabilities approach from the perspectives of Sen and Nussbaum, and the views of some authors on the contribution of this approach to university quality. The case study was implemented as a method of analysis; qualitative techniques were used to deepen the evaluations of people, such as semi-structured interviews, participant observation, and document review. We managed to analyze and discuss the evidence found in relation to the theoretical framework: the presence of the values of human development in philosophy and extension activities; a list of expanded capabilities through university policies; and the fact of highlighting that conversion factors (such as personal characteristics, environmental characteristics of the locations, and the presence of institutions) are crucial to the expansion of freedoms. Despite some weaknesses and challenges, we consider as highly important that Latin American universities keep the accompaniment to the local population as a determining factor for the human development of depressed communities.